A Pyroxenic View on Magma Hybridization and Crystallization at Popocatépetl Volcano, Mexico - Mangler, Martin F.; Petrone, Chiara M.; Hill, Samuel; Delgado-Granados, Hugo; Prytulak, Julie (Frontiers in Earth Science, 2020)
The Popocatépetl Volcanic Complex (PVC) is an active arc volcano located in central Mexico, 70 km southeast of Mexico City. Current models of the PVC’s plumbing system and magma petrogenesis are largely based on studies of isolated Plinian eruptions over the past 23.5 ka and present-day Vulcanian activity, while voluminous interplinian effusive summit and flank eruptions remain underrepresented. Here, we present a detailed petrological characterization focussed on ortho- and clinopyroxene in five effusive flank eruptions and two Plinian eruptions of the PVC during the last ∼14.1 ka. Texturally and compositionally defined pyroxene populations are used to constrain magmatic temperatures and deconvolve crystallization histories. At least two long-lived, inter-connected magmatic environments (ME) are identified in the mid- to upper crust beneath the PVC: (1) a mafic ME crystallizing high-Mg orthopyroxene + clinopyroxene + Cr-spinel ± sulfide at 1000–1115°C, and (2) an evolved, shallower ME crystallizing plagioclase + low-Mg orthopyroxene + clinopyroxene + Fe-Ti oxides + apatite ± sulfide at long-term storage temperatures of ∼970°C. The architecture of the PVC plumbing system has remained stable throughout the last ∼14.1 ka, and both MEs have sustained above-solidus magma storage temperatures fueled by recharge with hydrous, high-Mg basaltic mantle melts that crystallized fosteritic olivine + Cr-spinel + low-Ca clinopyroxene in the lower- to mid-crust at 1080–1220°C. Lavas and pumices show texturally and compositionally diverse crystal cargoes indicative of frequent magma mixing, with ≤67% of pyroxene crystals originating from the mid- to upper crustal mafic ME, of which ≤74% were stored and diffusively overprinted in the evolved ME for centuries to millenia. Pyroxene crystals of different origins, ages and thermal histories are stored in the evolved ME as a heterogeneous crystal mush that is frequently disrupted, reorganized and replenished by mafic injections. Magma recharge causes melt and crystal hybridization over timescales ranging from near-instantaneous to millenia, which produces the diverse crystal cargo and restricted whole-rock compositions typical for the PVC and many other arc volcanoes. We suggest that hot storage conditions and magma dynamics similar to the PVC may be characteristic for many other arc volcanoes of intermediate sizes and compositions.